2021
DOI: 10.15408/etk.v20i2.22045
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ICT in Women Empowerment and Achieving SDGs: A Case Study of Women Labor Force in Developing Countries

Abstract: The aim of the study is to analyze the ways women are empowered through information and communication technology (ICT) and fostering the process of achieving the Sustainable Development Goals (SDGs). Women in developing countries are facing economic and social hardships and have limited access to ICT, which in turn translate into their lack of skills, lower literacy rate and restricted social engagement. Therefore, present study explores the role of ICT on women empowerment in 51 developing countries by conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…A variety of studies in Asia have demonstrated that ICT can enhance women's empowerment (Manzoor & Farooq, 2017;Noor, Asghar & Arfeen, 2021;Patil, Dhere & Pawar, 2009). ICT can support the empowerment of women through capacity building, and women who do not have access to ICTs can be disempowered as they lack a voice and part in the information realm (Mackey & Petrucka, 2021).…”
Section: Women's Empowermentmentioning
confidence: 99%
“…A variety of studies in Asia have demonstrated that ICT can enhance women's empowerment (Manzoor & Farooq, 2017;Noor, Asghar & Arfeen, 2021;Patil, Dhere & Pawar, 2009). ICT can support the empowerment of women through capacity building, and women who do not have access to ICTs can be disempowered as they lack a voice and part in the information realm (Mackey & Petrucka, 2021).…”
Section: Women's Empowermentmentioning
confidence: 99%
“…Global literature effectively portrays how ICT has revolutionized our lives during the last twenty years. Research related to ICT has given rise to various streams of theoretical and empirical studies (Noor et al, 2021). Colecchia & Schreyer (2002); Iqbal et al (2019); Yakunina & Bychkov (2015) assert that ICT can significantly influence human development.…”
Section: Introductionmentioning
confidence: 99%